Off-label Use of the Optilume Drug-coated Balloon in the Treatment of Bladder Neck Stenosis and Vesicourethral Anastomosis Stenosis - Tosev, Georgi; Damgov, Ivan; Kuehhas, Franklin; Borgmann, Hendrik; Struck, Julian; Salem, Johannes; Kuru, Timur H. (European urology open science, 2025)
Bladder neck stenosis (BNS) and vesicourethral anastomosis stenosis (VUAS) are uncommon but clinically significant complications following transurethral surgery and radical prostatectomy (RP), often presenting important clinical challenges because of high recurrence rates with standard treatments. We retrospectively evaluated the efficacy of the Optilume paclitaxel-coated balloon in managing recurrent BNS and VUAS. Sixteen patients who had undergone open or robotic RP, transurethral resection of the prostate, or GreenLight laser photoselective vaporization of the prostate were assessed. At 12 mo after BNS/VUAS surgery, the International Prostate Symptom Score (IPSS), postvoid residual volume (PVR), and freedom from repeat intervention were evaluated. All patients remained free from repeat intervention and anatomic recurrence at 1-yr follow-up. Among the 16 patients (seven with preexisting incontinence), 12-mo follow-up demonstrated stable continence with no worsening, and all patients reported high satisfaction and willingness to repeat the procedure. Significant improvements in scores were observed for IPSS (p < 0.001; n = 16) and IPSS quality of life (t = 4.75, p < 0.001; n = 16), while PVR did not change significantly (p = 0.442; n = 8). These findings suggest that the Optilume paclitaxel-coated balloon is an effective off-label treatment for recurrent BNS and VUAS as applied in two urology practices in Germany, corroborating evidence from randomized controlled trials on the treatment of anterior urethral strictures. - Patient summary - We evaluated off-label use of the new drug-coated Optilume balloon for treatment of recurrent narrowing of the bladder neck or VA (vesicourethral anastomosis; surgical join between the bladder and urethra) in patients who had previously undergone prostate surgery. Our findings show that this treatment significantly improved urinary function assessed 1 year after the procedure and prevented the need for further surgeries.